1999
DOI: 10.1111/j.1502-3931.1999.tb00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of cenograms in mammalian palaeoecology. A critical review

Abstract: LETHAIA Rodriguez, J. 1999 12 15: Use of cenograms in mammalian palaeoecology. A critical review. Lethaia Vol. 32, pp. 331-347. Oslo. ISSN 0024-1164. Cenograms are graphic representations of the size distribution of the mammalian species present in a community and are used in palaeoecological studies to obtain information about the environment. Three empirical rules are commonly applied in the interpretation of cenograms. This paper reviews the methodology of cenograms, special attention being paid to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 27 publications
1
34
0
1
Order By: Relevance
“…The final dataset contained 4846 mammalian species within 62 biorealms and 796 ecoregions. Assemblage data came from a literature compilation of 242 species checklists [76,77] containing a total of 1911 species and representing 140 ecoregions; the lists were for non-volant mammals only, so Chiroptera (bats) were pruned from the trees prior to randomizations of assemblages within ecoregions. Because estimates of b from small datasets seemed highly variable, we excluded all samples with fewer than 20 species, leaving us with 59 biorealms, 728 ecoregions and 233 assemblages.…”
Section: The Geographical Scale Of Phylogenetic Imbalancementioning
confidence: 99%
“…The final dataset contained 4846 mammalian species within 62 biorealms and 796 ecoregions. Assemblage data came from a literature compilation of 242 species checklists [76,77] containing a total of 1911 species and representing 140 ecoregions; the lists were for non-volant mammals only, so Chiroptera (bats) were pruned from the trees prior to randomizations of assemblages within ecoregions. Because estimates of b from small datasets seemed highly variable, we excluded all samples with fewer than 20 species, leaving us with 59 biorealms, 728 ecoregions and 233 assemblages.…”
Section: The Geographical Scale Of Phylogenetic Imbalancementioning
confidence: 99%
“…In this aspect, Rickenbach may correspond to a warmer climate (Legendre 1987) probably linked to the Latest Oligocene Warming. However, Rodriguez (1999) demonstrated that the slope of the micromammals, which is correlated to the number of species, does not seem to be associated with temperature.…”
Section: Cenogram Analysismentioning
confidence: 99%
“…The habitat extrapolated from the mammalian community of Rickenbach is very similar to that of the wooded savannah of Lokori (Kenya) in the following points: very large mammals of class 5 (elephants and hippopotamuses), first break right after them, and second break. According to Rodriguez (1999), the fact that the second gap is smaller in Rickenbach than in Lokori could be due to a more wooded environment for the former. The similar number of small and very small mammals could indicate a similar warm climate (Legendre 1989).…”
Section: Cenogram Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cenograms have become a standard tool in mammalian paleoecology (Legendre 1986(Legendre , 1989Gingerich 1989;Ducrocq et al 1994;Gunnell and Bartels 1994;Maas and Kraus 1994;Montuire 1995Montuire , 1998Montuire , 1999Morgan et al 1995;Gibernau and Montuire 1996;Gunnell 1997;Montuire and Desclaux 1997;Dashzeveg et al 1998;Wilf et al 1998;Croft 2001;Montuire and Marcolini 2002;Storer 2003;Palombo et al 2005;Tsubamoto et al 2005;Geraads 2006;Gómez Cano et al 2006;Palombo and Giovinazzo 2006;Costeur and Legendre 2008), albeit with some reservations expressed (Rodríguez 1999). Graphs that plot the natural logarithm of body mass (in grams) of each species of non-volant, non-predatory mammal in a fauna against the decreasing rank order of each species' body mass in the fauna (Figure 1) are thought to reflect the structure of the vegetation and climate, but what interests us here is what cenograms show about the structure of large-herbivore faunas.…”
Section: Introduction: Really Big Herbivoresmentioning
confidence: 99%